Penyuluhan Merangsang Jiwa Kewirausahaan Kelompok Produktif Untuk Melahirkan Usahawan Muda Mandiri Di Kalangan Pemuda Dan Pemudi RW 023, Kelurahan Teluk Pucung , Kecamatan Bekasi Utara, Kota Bekasi - Endri sentosa; Mahmud Mahmud; Sarpan Sarpan; Herminda Herminda; Rufial Rufial (IKRA-ITH ABDIMAS, 2023)
It has been almost two years since the COVID-19 pandemic has been going on and during thattime this pandemic has changed the perspective and pattern of human life, including most Indonesianfamilies. After the period starts to improve, this is the time for youth to be so important in handlingCovid-19.Millennials are a generation that grew up in the booming internet era where they have differentcharacteristics of each individual, it depends on where he grew up, his family's economic and socialstrata, his communication patterns are very open compared to previous generations, fanatical socialmedia users and their lives. heavily influenced by technological developments. Likewise with theeconomy, which is increasingly competitive, requires the younger generation to be more creative anddynamic in increasing the value of local products. With the technological capabilities they have, theyounger generation can take advantage of these technological capabilities to increase effectiveness andefficiency in the management of MSMEs which have been managed traditionally and conventionally.MSMEs in the digital economy, from a total of 65.47 million MSME units, the Ministry ofCooperatives and SMEs noted that 17.25 million MSME actors were connected to the digital economyecosystem in February 2022 or around 26.4 percent.